2014
DOI: 10.3168/jds.2013-7212
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Genetic characterization of digital cushion thickness

Abstract: Dairy cow lameness is a serious animal welfare issue. It is also a significant cause of economic losses, reducing reproductive efficiency and milk production and increasing culling rates. The digital cushion is a complex structure composed mostly of adipose tissue located underneath the distal phalanx and has recently been phenotypically associated with incidence of claw horn disruption lesions (CHDL); namely, sole ulcers and white line disease. The objective of this study was to characterize digital cushion t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 31 publications
5
14
1
Order By: Relevance
“…Our research group has already shown that DCT is a strong predictor of lameness and highly associated with CHDL (Bicalho et al, 2009;Machado et al, 2011). We have also recently shown that part of this relationship is heritable and therefore it could be manipulated through genetic selection (Oikonomou et al, 2014). The results of the present study provide new information regarding the role of the digital cushion because we show here that DCT is associated with sole temperature.…”
Section: Discussionsupporting
confidence: 63%
“…Our research group has already shown that DCT is a strong predictor of lameness and highly associated with CHDL (Bicalho et al, 2009;Machado et al, 2011). We have also recently shown that part of this relationship is heritable and therefore it could be manipulated through genetic selection (Oikonomou et al, 2014). The results of the present study provide new information regarding the role of the digital cushion because we show here that DCT is associated with sole temperature.…”
Section: Discussionsupporting
confidence: 63%
“…However, a significant genomic effect was detected for DCT at calving, providing a moderate genomic heritability of 0.23 ± 0.12. When compared with the heritability of 0.33 obtained in a previous pedigree-based study (Oikonomou et al, 2014), our estimate was smaller but within the standard error boundaries.…”
Section: Discussionsupporting
confidence: 56%
“…This will affect the time cows spend on their feet and could potentially be associated with post-calving changes in SSTT (26). Work undertaken by Oikonomou et al (27) described a heritability estimate of 0.33 for SSTT, therefore genetics may also play a role in the inconsistences presented by these two studies. Contrary to the Newsome et al (17) study where the assessor measuring SSTT was blinded to stage of lactation, we assessed SSTT knowing whether the cows were at pre-calving, fresh, or EL stage.…”
Section: Discussionmentioning
confidence: 99%